Competition Kinetics of the Nonbranched-Chain Addition of Free Radicals to Olefins, Formaldehyde, and Oxygen - M. M. Silaev (International Journal of Chemical Engineering)
Five reaction schemes are suggested for the initiated nonbranched-chain addition of free radicals to the multiple bonds of alkenes, formaldehyde, and oxygen. The schemes include reactions competing with chain propagation through a reactive free radical. The chain evolution stage in these schemes involves three or four types of free radicals. One of them— CH2=C(CH3)•CH2, CH2=CH•CHOH, H•C=O, 𝑜−CH3C6H4CH2O•4, or HO•4—is relatively low-reactive and inhibits the chain process by shortening of the kinetic chain length. Based on the suggested schemes, nine rate equations containing one to three parameters to be determined directly are set up using quasi-steady-state treatment. These equations provide good fits for the nonmonotonic (peaking) dependences of the formation rates of the molecular addition products (1 : 1 adducts) on the concentration of the unsaturated component in liquid homogeneous binary systems consisting of a saturated component (hydrocarbon, alcohol, etc.) and an unsaturated component (olefin, formaldehyde, or dioxygen). The unsaturated compound in these systems is both a reactant and an autoinhibitor generating low-reactive free radicals. A similar kinetic description is applicable to nonbranched-chain free-radical hydrogen oxidation. The energetics of the key radical-molecule reactions is considered.